2018
DOI: 10.5171/2018.511388
|View full text |Cite
|
Sign up to set email alerts
|

Global Efforts of Tax Authorities and Tax Evasion Challenge

Abstract: The global economy has become more and more integrated, and the multinational corporations are increasing their share on the global trade. The global multinationals can benefit the most from the way how the tax systems are set up and thereby, they can minimalize the tax base leading to paying lower or none taxes. Tax evasions represent a global challenge for the tax authorities seeking the way to combat them. The European Union has announced that the value added tax leak is around 50 billion euros lately. Tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Under the economic factors, business sanctions, business stagnation, and the amount of tax burden are considered as influential factors. On the other hand, legal factors, social factors, demographic factors, mental factors, and moral factors are the most important factors (Saxunova and Szarkova, 2018). Many factors determine the taxpayers' interest to engage in tax evasion.…”
Section: Theoretical Reviews On Factors Affecting Tax Evasionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the economic factors, business sanctions, business stagnation, and the amount of tax burden are considered as influential factors. On the other hand, legal factors, social factors, demographic factors, mental factors, and moral factors are the most important factors (Saxunova and Szarkova, 2018). Many factors determine the taxpayers' interest to engage in tax evasion.…”
Section: Theoretical Reviews On Factors Affecting Tax Evasionmentioning
confidence: 99%
“…This statement confirmed that every citizen should be subjected to the law of tax, and they are obliged to pay the tax from their income. To build large dams, to construct transportation infrastructures, and to provide quality social services for the community, collecting a tax from citizens plays a significant role for the governments (Saxunova and Szarkova, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tax evasion has been a global phenomenon both in the developed and the emerging economies. Studies have established that tax evasion has become a universal threat in which the various governments and the respective tax authorities have been intensifying more efforts to minimize the effect on economic growth (Saxunova and Szarkova, 2018). Tax evasion is seen as money-spinning, which cost the United States of America an average of $458 billion per annum between 2008-2010 (Matthews, 2016).…”
Section: Literature Review Tax Evasion and Tax Compliance Enforcementmentioning
confidence: 99%
“…Tax evasion has been a global phenomenon both in the developed and the emerging economies. Studies have established that tax evasion has become a universal threat, which the governments and the respective tax authorities have intensified more efforts to minimize the effect on economic growth (Saxunova and Szarkova, 2018). Tax evasion is seen as money-spinning, costing the United States of America an average of $458 billion per annum between 2008-2010 (Matthews, 2016).…”
Section: Literature Review Tax Evasion and Tax Compliance Enforcementmentioning
confidence: 99%